Implementasi Penguatan Pendidikan Karakter (PPK) Pada Mata Pelajaran PJOK di Sekolah Dasar Islam Terpadu Kabupaten Lebong - Fatria Medika; Syafrial syafrial; Ari Sutisyana (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to describe the implementation of strengthening character education (PKK) in PJOK subjects. This research is a qualitative descriptive study. The method used in this research is a survey method. The instrument used was a questionnaire. The composed instruments were consulted with an expert (expert judgment). The subjects in this study were PJOK teachers and SDIT students of Lebong Regency with a total of 3 PJOK teachers and 45 students. The data analysis technique used is descriptive analysis with a percentage. The results showed that the implementation process of strengthening character education (PPK) in corner subjects at the Integrated Islamic Elementary School in Lebong Regency, namely the religious character value of 94%, the nationalist value 89%, the independent value 95%, the mutual cooperation value 94% and the integrity value 95% .